Possible role of imprinting in the Turner phenotype. Issue 11 (November 1994) - Chu, C E; Donaldson, M D; Kelnar, C J; Smail, P J; Greene, S A; Paterson, W F; Connor, J M
Abstract : We have attempted to investigate the role of imprinting in the phenotype of Turner's syndrome. Sixty-three patients were investigated for parental origin of the retained normal X chromosome; 43 were found to retain the maternal X (XM) and 20 the paternal (XP). The relationship between a child's pretreatment height centile and parental height centiles was examined in 36 patients. No significant correlation was found between child and parental height centiles for XP or child and paternal height centiles for XM (p > 0.05) but a strong correlation was found between child's height centile and maternal height centile (p < 0.01) for XM. Using pooled data from this and other studies there was no significant correlation with renal anomalies but a strong correlation between cardiovascular abnormalities and XM (0.01 > p > 0.001) and neck webbing and XM (p < 0.05). We conclude that imprinting may play a part in the Turner's syndrome phenotype, especially with respect to pretreatment height, cardiovascular anomalies, and neck webbing.